2018
DOI: 10.4081/ejtm.2018.7594
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance in patients suffering from nosocomial infections in Besat Hospital

Abstract: This study was performed to determine the trend of antibiotic resistance of the causative organisms among the patients suffering from nosocomial infections in Besat Hospital since 2013 to 2015. In this observational study that was performed as a retrospective cohort, 935 consecutive patients with nosocomial infection were enrolled in Besat Hospital since 2013 to 2015. The trend of antibiotic resistance of the causative organisms among them was determined and contributing factors were assessed. The finding of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 9 publications
0
14
0
2
Order By: Relevance
“…Studies have also shown that microbes become highly resistant to overconsumption of antibiotics. Study of Hormozi et al (2018), showed that antibiotic resistance has an increasing trend and strategic measures of prevention are needed to reduce nosocomial infections. 16 Therefore, a positive step can be taken to improve hospital preparedness by Infection prevention and control (IPC) programs such as hand hygiene, sterilization, cleaning, disinfection, personal protective equipment and restrictions on the wide use of antibiotics and developing treatment protocols for antibiotic use, as well as developing biological triage and appropriate treatment protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also shown that microbes become highly resistant to overconsumption of antibiotics. Study of Hormozi et al (2018), showed that antibiotic resistance has an increasing trend and strategic measures of prevention are needed to reduce nosocomial infections. 16 Therefore, a positive step can be taken to improve hospital preparedness by Infection prevention and control (IPC) programs such as hand hygiene, sterilization, cleaning, disinfection, personal protective equipment and restrictions on the wide use of antibiotics and developing treatment protocols for antibiotic use, as well as developing biological triage and appropriate treatment protocols.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of HBsAg in the blood or serum sample signifies a chronic and acute level of hepatitis B virus infection [30,31]. The operating principle involves labeling the AuNR surface with a monoclonal hepatitis B surface antibody (HBsAb) to detect HBsAg and the technique was validated via ELISA [32]. Integrating the antibody with concentrated AuNRs through nonspecific physisorption lead to the synthesis of the antibody-AuNR complex ( Figure 2) called the biosensor, which can characterize target proteins.…”
Section: Application Of Aunp In Detecting Hb Surface Antigenmentioning
confidence: 99%
“…The presence of HBsAg in the blood or serum sample signifies a Gold Lymph nodes in mouse [63] Brain vessels in mouse [64] HER2 cancer biomarker in breast adenocarcinoma cells [65] This chronic and acute level of hepatitis B virus infection [30,31]. The operating principle involves labeling the GNR surface with a monoclonal HBsAb to detect HBsAg and the technique was validated via ELISA [32]. Integrating the antibody with concentrated GNRs through nonspecific physisorption lead to the synthesis of the antibody-GNR complex (Figure 2) called the biosensor, which can characterize target proteins.…”
Section: Application Of Gold Nanoparticle In Detecting Hb Surface Antmentioning
confidence: 99%